Risk-stratified optimization of skin care protocols for children with cardiac monitors: a data-driven clinical framework - Zhang, Kun; Chen, Ning; Yuan, Hui (Frontiers in Pediatrics, 2025)
ObjectiveTo develop a risk-stratified nursing protocol reducing electrode-related skin injuries (MARSI) in pediatric cardiac monitoring.MethodsUsing logistic regression, we analyzed risk factors (allergy history, eosinophil indices, wear duration) in 229 control-group children (June to August 2023) receiving standard care. Derived protocol integrated risk thresholds. Validation involved 183 intervention-group children (September to December 2023).ResultsSkin injury correlated negatively with age/weight/height/BMI (p < 0.05) and positively with allergy history/wear time/eosinophils (p < 0.05). The intervention group showed significantly lower MARSI incidence (15.8% vs. 40.6%, p < 0.001), with reduced redness (4.2% vs. 32.8%) and rashes (2.1% vs. 9.2%) (p < 0.05).ConclusionThis risk-stratified nursing protocol reduces pediatric MARSI incidence, supporting clinical implementation.